2012
DOI: 10.1097/prs.0b013e318241289c
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Regeneration by Micrograft Transplantation with Immediate 100-Fold Expansion

Abstract: Minced skin micrografts are very effective in wound repair and can provide 100-fold expansion of a skin graft. Early clinical results confirm the utility of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Most of these early attempts were associated with labor‐intensive or time‐consuming methodology, which limited widespread adoption of this therapeutic approach . Lately, there has been a push towards developing modifications of autologous skin grafts to address limitations of STSG and pitfalls of early attempts in micrografting . In a study conducted by Hackl et al, skin micrografts 0.8 mm 2 in size were transplanted and spread evenly over a full‐thickness wound bed with the expansion ratio of 1:100 .…”
mentioning
confidence: 99%
“…Most of these early attempts were associated with labor‐intensive or time‐consuming methodology, which limited widespread adoption of this therapeutic approach . Lately, there has been a push towards developing modifications of autologous skin grafts to address limitations of STSG and pitfalls of early attempts in micrografting . In a study conducted by Hackl et al, skin micrografts 0.8 mm 2 in size were transplanted and spread evenly over a full‐thickness wound bed with the expansion ratio of 1:100 .…”
mentioning
confidence: 99%
“…This did not include full‐thickness skin, however. Since then many alternative techniques have been developed to apply this concept, including mincing split‐thickness grafts into smaller pieces (Meek, ; Hackl et al , ) and enzymatically digesting split‐thickness skin into single‐cell suspensions (Fraulin et al , ; Navarro et al , ). These techniques also fail to transfer full‐thickness skin structures, and lead to a donor site wounds that heal with scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, there are many existing clinical options for providing temporary barrier function, from various bandages and dressings to advanced biomaterials. In particular, dressing regimens that maintain a moist wound environment have been shown to enable the engraftment of split‐thickness skin grafts with no detrimental effects, even when the grafts were placed upside‐down, as keratinocytes are able to migrate from the base of the wound up to the surface, where they then participate in wound re‐epithelialization (Hackl et al , ; Zuhaili et al , ). This is salient because the skin columns in our study reported here were also applied randomly into wounds, without maintaining the epidermis‐up orientation of normal skin.…”
Section: Discussionmentioning
confidence: 99%
“…Zuhaili et al demonstrated that in a wet environment split‐thickness skin grafts can survive even when placed with the dermis facing away from the wound surface. Hackl et al showed that a wet or a moist environment improved reepithelialization and decreased contracture in wounds treated with minced skin micrografts and further demonstrated that the micrografts survived regardless of orientation (dermis up or down).…”
Section: Hydrationmentioning
confidence: 99%